Perkembangan Psikososial Anak Pada Keluarga Buruh Migran Internasional Di Wilayah Kabupaten Kendal - Nurhidayati, Tri; Rahayu, Desi Ariyana; Mubin, M. Fatkul (Jurnal Keperawatan Jiwa, 2014)
This study aims to to identify psychosocial development of the children. It is based on several studies that families become overburdened with children entrusted, the child's relationship with her mother became strained, unruly children and school dropouts. Family is the first level of social group, the first place for learning about values and the formation of the child's personality structure through the values and norms of the parents. Yet with his parents, especially mothers working abroad will have much effect on the child. Problems that are often experienced by children whose parents work abroad (especially mothers) migrated abroad to earn money for the family, many children who pass through the golden age without the guidance of a mother, even though this period determine the most critical period for children. Though the mother would not be replaced by anyone. Children who left a lot of experience psychosocial problems such as emotional disorders, behavioral problems, hyperactivity, tend to be more passive in terms of addressing issues that arise both families and schools. The study was conducted in the area of Kendal, precisely at Taman Gede village, Gemuh subdistrict. Taman Gede is one of the villages in the district, which send many citizens working abroad according to one of the company's most labor suppliers at Gemuh districts. Kendal selected based on the results BNP2TKI report stating that Kendal area was ranked as the ninth highest labor suppliers in Indonesia in 2012.Respondents are selected based on inclusion criteria that is international migrant worker's family with family members (mother) who left children aged 0 -18 years. The research used descriptive method design to analyze and describe the psychosocial development of the children. Analysis using univariate analysis. The results of the study were obtained either psychosocial development of the child as many as 24 people (60%). Unfavorable psychosocial development that have familiar friends play have significant achievements in life.